Characterization of the Promoter Region of Biosynthetic Enzyme Genes Involved in Berberine Biosynthesis in Coptis japonica - Yamada, Yasuyuki; Yoshimoto, Tadashi; Yoshida, Sayumi T.; Sato, Fumihiko (Frontiers in Plant Science, 2016)
The presence of alkaloids is rather specific to certain plant species. However, berberine, an isoquinoline alkaloid, is relatively broadly distributed in the plant kingdom. Thus, berberine biosynthesis has been intensively investigated, especially using Coptis japonica cell cultures. Almost all biosynthetic enzyme genes have already been characterized at the molecular level. Particularly, two transcription factors (TFs), a plant-specific WRKY-type transcription factor, CjWRKY1, and a basic helix-loop-helix (bHLH) transcription factor, CjbHLH1, were shown to comprehensively regulate berberine biosynthesis in C. japonica cells. In this study, we characterized the promoter region of some biosynthetic enzyme genes and associated cis-acting elements involved in the transcriptional regulation via two TFs. The promoter regions of three berberine biosynthetic enzyme genes (CYP80B2, 4’OMT and CYP719A1) were isolated, and their promoter activities were dissected by a transient assay involving the sequentially truncated promoter::luciferase (LUC) reporter constructs. Furthermore, transactivation activities of CjWRKY1 were determined using the truncated promoter::LUC reporter constructs or constructs with mutated cis-elements. These results suggest the involvement of a putative W-box in the regulation of biosynthetic enzyme genes. Direct binding of CjWRKY1 to the W-box DNA sequence was also confirmed by an electrophoresis mobility shift assay (EMSA) and by a chromatin immunoprecipitation (ChIP) assay. In addition, CjbHLH1 also activated transcription from truncated 4’OMT and CYP719A1 promoters independently of CjWRKY1, suggesting the involvement of a putative E-box. Unexpected transcriptional activation of biosynthetic enzyme genes via a non-W-box sequence and by CjWRKY1 as well as the possible involvement of a GCC-box in berberine biosynthesis in C. japonica are discussed.